Pengaruh Persepsi Pelaksanaan Sensus Pajak Nasional, Kesadaran Perpajakan dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak di Lingkungan Kantor Wilayah Direktorat Jenderal Pajak di Semarang (Students' Journal of Accounting and Banking, 2014)
This study aims to analyze the factors that influence taxpayer compliance within the Regional Office of Directorate General of Regional Tax Semarang which includes the implementation of a national tax census perception, awareness and quality of service tax.This study used a survey design with questionnaire as an instrument. Respondents in this study is that the taxpayer has been sensus or do not have NPWP. Samples were processed in this study were 100 questionnaires. Respondents were surveyed using sampling that an individual taxpayer or entity in the business district, or office. Because the region is a priority target implementation of national tax census, registered taxpayers who have had stickers national tax census. Data analysis was performed using multiple linear regression analysis with SPSS for Windows 19.The results found that all the independent variables, namely the implementation of the National Tax Census perception, awareness Taxation, and Service Quality and significant positive effecton Taxpayer Compliance.Keywords: Perception of the Implementation of the National Tax Census, Tax Awareness, Quality Service, Taxpayer Compliance